A multichannel AOM for a holographic video system - Son, JY; Shestak, SA; Kim, SK; Epikhin, V; Chun, YS (KOREAN PHYSICAL SOC, 1998)
Many trapezoidally shaped AOMs are joined together to make a multichannel AOM having an aperture length equal to the sum of those of trapezoidally shaped AOMs. A trapezoidally shaped AOM has to have a definite angle between the long parallel and the two non-parallel edges to convert a longitudinal wave propagating normal to the two parallel edges to a shear wave travelling parallel to the edges, and vice versa, with maximum efficiency. For che case of an AOM made from TeO2, a acoustic-mode conversion efficiency of more than 90% was obtained when the angle was 82.33 degrees The performance of the multichannel AOM was tested by combining 6 TeO2 AOMs together with a gap between them of 300 mu m. The holographic fringe data was segmented into 6 equal parts and then inputted to the corresponding AOM. The holographic images were reconstructed by periodical illumination of the multichannel AOM with a green (lambda=0.5145 mu m) pulsed laser beam. The good-quality reconstructed images indicated that the multichannel AOM was working properly.